The Swiss and the South African Public Interest Tests in Competition Law - Two Systems compared - Frey, Marcel (Department of Commercial Law, 2014)
This paper will illustrate the South African and Swiss Competition Acts with a specific focus on the public interest consideration common to both. It will investigate if and how political considerations enter into the weighting of the abstract term of public interest and whether South Africa as the less developed country can learn anything from the Swiss system. In order to arrive at a better understanding of the two countries' systems, this paper will include a short introduction to the historical development of competition law in both countries as well as a description of their respective legislative backgrounds. I will then analyse the various decisions, which have been handed down by the competition authorities, specifically with regard to the public interest grounds inherent in both systems. The thesis will deal mainly with South African merger control cases, where the South African Competition Act expressly requires a balancing of public interest with commercial and competition interests. Unlike the situation in Switzerland, there is an abundance of case law on these issues in South Africa. I will attempt to distil the relevant discernable rules or consistent approaches in both countries' decisions.